MANAGEMENT OF PATIENTS WITH PROLONGED TYPES OF ACUTE SINUSITIS - E.Yu. Radtsig; N.V. Ermilova; N.A. Lobeeva; M.R. Bogomil'sky ("Paediatrician" Publishers LLC, 2008)
The questions of etiology, classification and management of children with sinusitis are discussed in this article. Special attention was given to the tactics of management of patients with permanent claims after standard course of medical treatment. Possible schemes of management of these patients and the results of proper clinical trial were presented. Key words: children, acute sinusitis, treatment.